PHYSICAL PROPERTIES OF PHOTOELECTRIC SOLAR CELLS BASED ON AlGaAs/GaAs SEMICONDUCTOR HETEROSTRUCTURES - Toshpulatova Dildora Khydarkulovna; Ubaydullaev Sadulla (Web of Journals Publishing, 2024)
A comparative analysis of the prospects of creating ultra - thin, light and highly efficient solar cells based on AlGaAs/GaAs heterostructures was conducted. Technological challenges and prospects for each option are discussed. A micron - scale thinning of AlGaAs/GaAs heterostructures using efficient technological methods has been proposed, which has been shown to significantly increase the yield percentage of solar cells.
Keywords: heterostructure, solar energy, alternative energy sources, electricity, photovoltaics, solar cell, monocrystalline and polycrystalline silicon, cascade elements, amorphous silicon, solar module.